Manual de lectura y escritura universitarias Práctica de taller - NOGUEIRA, Silvia comp. (BIBLOS, 2004)
Otros autores: ALZRAKI, Ruth; ALONSO SILVA, María Teresa; GANDARA, Santiago; GRIGUELO, Santiago; MAZZA, Claudia; ORNANI, Carla; TOSCANO Y GARCIA, Guillermo; VARELA, Leonardo; WARLEY, Jorge